Advertising and Its Effects on Consumer Behaviour in Kathmandu Valley - Neupane, Rajeswor (NCC Journal, 2019)
Nowadays, advertisement is considered as one of the most message medium to influence buying habit of the consumer. This study aims to answer the questions that whether the demographic background of ultimate consumeri.e. Age, gender, education and occupation has a varying effect on the media preference due to advertisements. The sample of 115 questionnaires we redistributed and out of these 110 responses recorded and compared. The result indicated that respondents like preferred TV advertisements have been found more popular as compared to Radio, Print and other media.